1995
DOI: 10.1007/bf01521344
|View full text |Cite
|
Sign up to set email alerts
|

Responses to T cell receptor/CD3 and interleukin-2 receptor stimulation are altered in T cells from B cell non-hodgkin's lymphomas

Abstract: T cells infiltrating (T-TIL) B cell non-Hodgkin's lymphomas (NHL) are thought to represent a local host response to the tumor. However, tumor progression in the presence of this T cell infiltrate suggests that the T-TIL may be functionally impaired. To address this issue we determined whether response to stimulation of T-TIL from 25 patients with NHL through the T cell receptor (TCR/CD3) and the interleukin-2 (IL-2) receptor (IL-2R) was intact, since activation of these receptors is important for proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that lymphoma B cells are resistant to CTL-mediated cell death (3)(4)(5), and this has been attributed to changes in their genetic or protein expression profile (3-5, 13, 14) as well as to abnormal CTL function (15)(16)(17). Additionally, there is accumulating data suggesting that T reg cells are capable of inhibiting CD8 + T cells under different pathologic conditions such as infection (18,19) or allograft transplantation in vivo (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that lymphoma B cells are resistant to CTL-mediated cell death (3)(4)(5), and this has been attributed to changes in their genetic or protein expression profile (3-5, 13, 14) as well as to abnormal CTL function (15)(16)(17). Additionally, there is accumulating data suggesting that T reg cells are capable of inhibiting CD8 + T cells under different pathologic conditions such as infection (18,19) or allograft transplantation in vivo (20,21).…”
Section: Introductionmentioning
confidence: 99%